Peran Penyuluh Agama dalam Pencegahan dan Pemberantasan Penyalahgunaan Narkotika di Kabupaten Gianyar - Haryawan, I Made (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper reviews the role of religious counselors in preventing and combating drug abuse in Gianyar Regency. The writing method used is qualitative with a descriptive analysis approach to relevant literature, policy documents, and case studies illustrating best practices in engaging religious figures. The findings indicate that religious counselors have significant potential as agents of change by strengthening moral and spiritual values, providing religious-based education on the dangers of narcotics, and facilitating cross-sector collaboration.   The analysis reveals that while the existence of Gianyar Regency Regional Regulation No. 1 of 2023 on P4GN (Prevention, Eradication, Misuse, and Illicit Trafficking of Narcotics) and Bali Governor Regulation No. 2 of 2018 provides a strong policy foundation, their implementation at the community level remains suboptimal. Based on an analysis of effectiveness, efficiency, and long-term impact (Dunn, 1999), it was found that the Formation of Technical Guidelines for Strengthening the Role of Religious Counselors in the P4GN Program by the Regional Office of the Ministry of Religious Affairs (Kanwil Kemenag) of Bali Province is the most promising policy alternative. The primary recommendation is for the Kanwil Kemenag Bali Province to immediately issue these technical guidelines, followed by comprehensive training for religious counselors. This will enable them to become effective agents of change in educating the community and reducing stigma, thereby supporting sustainable drug prevention and rehabilitation efforts in Gianyar.